Informed consent management guidance model of regional anesthesia: Education of young doctors in Teaching Hospitals - Titin Setyowati; Aisyah Lahdji (Universitas Muhammadiyah Surabaya, 2022)
Informed consent is not necessarily a guarantee for a hospital or health service to avoid disputes between the health provider and the recipient of the health service. This can be caused by the disruption of communication that is less effective and efficient where an Anesthesia Co-Assistant is less clear in delivering the informed consent problem so that the patient has another understanding of what the Anesthesia Co-Assistant is saying. So it takes guidance for Co-Assistant Anesthesia to have comprehensive abilities about a) understanding of regional anesthesia, b) understanding of regional anesthetic techniques, c) understanding of indications and contraindications, d) understanding of drug pharmacology, e) understanding of how to deal with complications, f) understanding of effective communication with patients.